Design of a Robotic Gripper by using Multi-objective Optimization Vibrating Particles System Algorithm - Lara-Molina, Fabian A.; Andrade, Jéssica Cristiane; Lobato, Fran Sérgio (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
In this contribution, the optimum forces extracted by a robot gripper on the surface of a grasped rigid object are determined. For this purpose, a multi-criteria optimization problem is formulated and solved by using the Multi-objective optimization Vibrating Particles System (MOVPS) algorithm. This numerical strategy is based on the association between the Vibrating Particles System (VPS) algorithm and three operators: Pareto dominance, crowding distance and mutation strategy. In addition, the proposed algorithm considers an external repository used to help the convergence during the evolutionary process. The objectives involve minimizing the difference between maximum and minimum gripping forces and simultaneously minimizing the transmission ratio between the applied gripper actuator force and the force experienced at the gripping ends. The results indicate that the proposed methodology surpasses the optimal solution of the previous study. However, without an increase in number of objective function evaluations.